Local Wisdom and Its Implications in Plant Diversity Conservation in Springs Area (Study Case in Ngenep Village, Karangploso District, Malang Regency) - Nunung Laili Nur Khasanah; Bagyo Yanuwiadi; Jati Batoro (Indonesian Journal of Environment and Sustainable Development, 2020)
Water from springs in Ngenep Village has an important role in people's lives. As an effort to protect the springs, the community sacred the springs. This study aims to analyze the local wisdom of the community in the conservation of springs and its implications for plant diversity in the spring area. Information related to local wisdom in the preservation of springs is done by searching the literature, spring area surveys and in-depth interviews. The diversity of plants in the spring has been done by plotting. Analysis of plants found in the spring is calculated relative density, relative frequency, relative dominance and plant value index for each spring. The Ngenep community divides springs into two terms namely springs with the terms "umbulan" and "belik". In Ngenep Village three springs are still maintained because they are springs that have cultural values in the community. Springs are Ngenep, Nyolo and Soko Springs. Each of these springs is located in a specific area of land with relatively natural vegetation. This spring is different from other regions in the rural landscape. this spring is a land that is not used for agricultural cultivation or settlement, but is a land that is conserved so that it is relatively natural. Among the plants of this type of tree that have the highest importance index value are the plants of S. pycnanthum, F. annulata, F. benjamina and S. indica. these plants can only be found in the spring area and on the river cliffs.